PERAN PEMERINTAH DESA WAY HUWI KABUPATEN LAMPUNG SELATAN DALAM MEWUJUDKAN DESA MANDIRI MELALUI PROGRAM KETAHANAN PANGAN - Ahmad Syarkati Azan; Fitri Yanti; Hasan Mukmin; Jasmadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Food needs are the most basic thing for human life and are the driving force of the world economy. As the level ofhuman life increases, the need for food will increase. The Qur'an as the holy book of Muslims who will alwaysṣaliḥ li kulli zamᾱn wa makᾱn, can be a problem solving, the spirit of Islam that must be present in food matters sothat deviations do not occur. The state to the village level must be able to regulate the availability of food it has, inorder to avoid a food crisis. Like in Way Huwi Village, Jati Agung District, South Lampung Regency, a foodsecurity program has been carried out in an effort to realize an independent village with a community developmentapproach. The implementation of community development through a food security program is an effort to realizean independent village in Way Huwi Village in implementing the program in Way Huwi Village, in general theprogram is running well, right on target, an effective program. This program goes through the stages carried out.First, the village deliberation, this stage is the initial stage, namely absorbing residents' aspirations, reading needs,mapping needs and priority scales in each hamlet so that the program carried out by the village is effective. Second,Village Development Planning Deliberation (Musrenbangdes) Musrenbangdes is driven by the VillageConsultative Body (BPD), is a routine agenda carried out before the program is implemented in order to uphold thespirit of deliberation by inviting various elements of village officials, Bhabinkamtibmas, Babinsa, communityleaders, religious leaders, LPM, youth organizations, posyandu cadres, and others. If the program has beendiscussed and reached an agreement, the next stage is program socialization including the food security program.Third, program socialization, this program socialization is carried out such as when it will be implemented, theprogram flow is announced so that activities run massively, socialization is carried out formally and informally,formal such as being posted on a notice board, informal such as when patrols, community service and othercommunity activities are conveyed by village officials to the community. Four Determination of BeneficiaryFamilies and Types of Businesses. Five, Implementation of Activities. Food security activities in Way HuwiVillage such as in the form of animals, vegetables and plants, the background is that most of the farmers are used toraising goats, cultivating fish, planting vegetables so this program is very suitable to be implemented. The role ofthe Way Huwi Village apparatus is also very significant in always monitoring the progress of the development ofbeneficiaries such as those who raise and enlarge goats, cows as well as vegetable plants and fruit seeds. Theauthor's recommendation in this study is to optimize cooperation with related parties such as the Regency,Provincial, House of Representatives, Agencies and Companies that are willing to help smooth this activity so thatthe beneficiaries are wider and more. The monitoring team continues to monitor with written reports so that it iseasy to monitor. Then collaborate with experts or facilitators so that community development continues with newinnovations to realize an independent village in Way Huwi Village, Jati Agung District, South Lampung Regency.